Tadeusz Tomasz Krasnodębski, Policjant konspiratorem. Szesnaście lat na muszce Gestapo i bezpieki [Policeman-Conspirator. Sixteen years on a sight of Gestapo and State Security] - Jan Grabowski (Zagłada Żydów)
The book Policjant konspiratorem (a beautiful edition, in hardcover, with an art paper insert with photographs) is quite an unusual document, if only because it is the first autobiography of a blue policeman that I ever heard of. Let us begin with the author: Krasnodębski was born in Wolbórz near Piotrków Trybunalski in 1916. In the late 1930s he graduated from the police school in Mosty Wielkie and shortly before the war broke out he was on duty as a constable in Dąbrowa Tarnowska. In autumn 1939 he volunteered for the blue police and remained in the force until summer 1944. At the same time, as an underground soldier, under the pseudonym “Kostek”, he was active in the Armed Combat Union (Związek Walki Zbrojnej, ZWZ), and later in the Home Army (Armia Krajowa, AK); he infiltrated the police, forewarning his “forest” commanders about the enemies’ moves. In summer 1944, “Kostek” deserted from the police and joined the partisans. After the Red Army’s arrival, Krasnodębski was still in the underground, this time in the NIE organization and in Freedom and Independence (Zrzeszenie Wolność i Niezawisłość, WiN). He was in hiding until the early 1950s, when he was brought before a court and accused of collaboration and murdering Jews. He was, however, exonerated and returned to normal life; he devoted himself to professional work as well as patriotic and veteran’s activity. He wrote the autobiography in the mid-1980s. This is the author’s fate in a nutshell.